" ... A Surprise ... for our readers!" : International artists' book exhibition. (Székesfehérvár : Szent István Király Múzeum, 1987)
Lakner, Laszlo ; Carothers, Martha ; Broel, Elisabeth ; Turner, Susan ; Bleus, Guy ; Dreisler, Guillermo ; Miccini, Eugenio ; Lohr, Helmut ; Savoi, Alba ; Zsigmond, Karolyi ; etc.
" ... A Surprise ... for our readers!" : International artists' book exhibition / " ... Meglepetés ... olvasóink részére! : "Nemzetközi muvészkönyv-kiallitás, Szent István Király Múzeum, Székesfehérvár, (Musée Roi Saint-Etienne), 18. octobre - 7. décembre 1987. Our exhibition is dedicated to the memory of Lajos Kassák born 100 years ago.
Engels-Hongaars
kunstcatalogus
Keywords: Kassák, Lajos